Selective HDAC6 inhibitor TubA offers neuroprotection after intracerebral hemorrhage via inhibiting neuronal apoptosis - Peng, Cuiying; Gong, Xiyu; Hu, Zhiping; Chen, Chunli; Jiang, Zheng (PeerJ, 2023)
A large body of evidence has demonstrated that neuronal apoptosis is involved in the pathological process of secondary brain injury following intracerebral hemorrhage (ICH). Additionally, our previous studies determined that the inhibition of HDAC6 activity by tubacin or specific shRNA can attenuate neuronal apoptosis in an oxygen-glucose deprivation reperfusion model. However, whether the pharmacological inhibition of HDAC6-attenuated neuronal apoptosis in ICH remains unclear. In this study, we used hemin-induced SH-SY5Y cells to simulate a hemorrhage state in vitro and adopted a collagenase-induced ICH rat model in vivo to assess the effect of the HDAC6 inhibition. We found a significant increase in HDAC6 during the early stages of ICH. As expected, the acetylated α-tubulin significantly decreased in correlation with the expression of HDAC6. Medium and high doses (25, 40 mg/kg) of TubA, a selective inhibitor of HDAC6, both reduced neurological impairments, histological impairments, and ipsilateral brain edema in vivo. TubA or HDAC6 siRNA both alleviated neuronal apoptosis in vivo and in vitro. Finally, HDAC6 inhibition increased the level of acetylated α-tubulin and Bcl-2 and lowered the expression of Bax and cleaved caspase-3 post-ICH. In general, these results suggested that the pharmacological inhibition of HDAC6 may act as a novel and promising therapeutic target for ICH therapy by up-regulating acetylated α-tubulin and reducing neuronal apoptosis.
Keywords: HDAC6; Acetylation of α-tubulin; Tubastatin A; Intracerebral hemorrhage; Apoptosis